2009
DOI: 10.1017/s0143385709000364
|View full text |Cite
|
Sign up to set email alerts
|

Iteration of certain meromorphic functions with unbounded singular values

Abstract: Abstract. Let M = { f (z) = (z m /sinh m z) for z ∈ C | either m or m/2 is an odd natural number}. For each f ∈ M, the set of singularities of the inverse function of f is an unbounded subset of the real line R. In this paper, the iteration of functions in one-It is shown that, for each f ∈ M, there is a critical parameter λ * > 0 depending on f such that a period-doubling bifurcation occurs in the dynamics of functions f λ in S when the parameter |λ| passes through λ * . The non-existence of Baker domains and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…By taking f 3 (z) = λ(z m /sinh m ), m or m/2 is an odd natural number and λ is any non-zero real number, it is observed that O f3 = {0}. A critical parameter λ * > 0 is found in [12] such that for |λ| > λ * , F(f 3 ) is the basin of attraction or parabolic basin corresponding to a 2-periodic point and 0 ∈ F(f 3 ). Further, it is proved that all the Fatou components are simply connected which means that J (f 3 ) is connected.…”
Section: Resultsmentioning
confidence: 99%
“…By taking f 3 (z) = λ(z m /sinh m ), m or m/2 is an odd natural number and λ is any non-zero real number, it is observed that O f3 = {0}. A critical parameter λ * > 0 is found in [12] such that for |λ| > λ * , F(f 3 ) is the basin of attraction or parabolic basin corresponding to a 2-periodic point and 0 ∈ F(f 3 ). Further, it is proved that all the Fatou components are simply connected which means that J (f 3 ) is connected.…”
Section: Resultsmentioning
confidence: 99%
“…The initial study of iterations of transcendental meromorphic functions is mainly found in [1,2,3,5]. Further, researches in this direction are pursued in [7,13,18,26]. Since the Julia sets (chaotic sets) occur as one of the crucial component in these investigations, their various characterizations and identification of their intrinsic properties are primarily developed in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…And the dynamics of function λ e z −1 z , λ > 0 is investigated by Kapoor and Prasad [3]. Further, the dynamics of certain transcendental meromorphic functions with unbounded singular values was explored by Nayak and Prasad [5]. Especially in [8], Sajid and Alsuwaiyan studied chaotic behavior in the real dynamics of a one parameter family of non linear function λ xe x x−1 , λ > 0, x ∈ R {1}.…”
Section: Introductionmentioning
confidence: 99%